Mineral contents of Acacia mangium Willd under defoliation conditions - Clavero, T.; Miquelena, E.; Rodríguez Petit, A. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2011)
In an Acacia mangium Willd plantation, located in the western part of Venezuela, a trial was carried out to assess the mineral content of leaves of cacia mangium under three defoliation frequencies (6, 9 and 12 weeks) and three defoliation heights (50, 75 and 100 cm). The factors studied were combined in a factorial arrangement of a random block design with three replications. There were significant differences (P < 0.05) for the frequency and height of defoliation on the concentrations of K, Mn and Zn. The data showed that levels of Ca, Mg, Na and P were affected by maturity. Mineral contents redution with advancing maturity may be due to a natural dilution process.